Effect of Goggle Slippage on the Video Head Impulse Test Outcome and Its Mechanisms. Issue 1 (January 2017) - Suh, Myung-Whan; Park, Jae Hong; Kang, Seong Il; Lim, Jae Hyun; Park, Moo Kyun; Kwon, Seong Keun
Abstract : Objectives: The aim of this study was to quantitatively measure the tightness of the goggle strap during the video head impulse test (vHIT) and to identify slippage-induced artifacts according to tightness. We aimed to elucidate the mechanism of faulty gain caused by goggle slippage and explain the typical artifacts associated with it. Subjects and Methods: An endotracheal tube cuff manometer was coupled to the EyeSeeCam vHIT system (Interacoustics, Assens, Denmark) to monitor strap tightness. The instantaneous gain (40, 60, and 80 ms) and regression gain were compared in eight healthy subjects under the following strap tightness conditions: loose (25 cm H2 O), tight (35 cm H2 O), and very tight (45 cm H2 O). To elucidate the mechanism of faulty gain caused by goggle slippage, a fake fixed pupil with a vestibule ocular reflex (VOR) gain of 0 was attached to the subject's eyelid. The faulty gain recording pattern was analyzed as the tightness of the strap was decreased. Results: The most common slippage-induced artifacts were: 1) initial backward eye movement toward the head movement, 2) acceleration bumps, 3) high gain, and 4) deceleration bumps. At 40 ms, the gain was significantly lower in the 25 cm H2 O condition (0.68 ± 0.32 cm H2 O) compared with the 45 cm H2 O condition (0.90 ± 0.26 cm H2 O). At 80 ms, the gain was higher for the 25 cm H2 O condition (1.24 ± 0.27 cm H2 O) compared with the 45 cm H2 O condition (1.16 ± 0.30 cm H2 O). These findings were progressively more obvious as the tightness of the strap decreased in a dose-dependent manner. When the fake pupil was recorded, initial backward eye movement toward the head movement (negative VOR gain) and eye tracing mimicking a small VOR (positive VOR gain) were recorded, despite the fake pupil having absolutely no movement. These artifact recordings are presumed to be related to the faulty low (40 ms) and high (80 ms) gain calculation. Conclusions: Slippage-induced artifacts are presumed to be because of the slingshot-like movement of the goggles during head movement in three different phases (lagging, overshooting, and bouncing of the goggles). Monitoring the pressure of the strap tightness may be a solution for minimizing this slippage. A strap tightness of at least 45 cm H2 O is required for reliable vHIT recording and gain calculations. Abstract : Supplemental Digital Content is available in the text